Biogenic hydroxyapatite-zinc oxide nanocomposites: A synergistic strategy for antibacterial and osteoconductive coatings on orthopedic implants - Fatemi, Mohaddeseh; Bahrami, Zohreh; Bahraminasab, Marjan; Nabizadeh Chianeh, Farideh (Heliyon, 2025)
Improving the biointegration of orthopedic implants with surrounding tissues is a key focus in biomaterials science. However, surfaces that enhance osteointegration may also promote bacterial colonization, leading to infections. Therefore, it is essential to balance the need for bacterial resistance with the promotion of cell attachment for osteointegration, particularly for titanium and its alloys. This investigation aimed to study the feasibility of co-depositing natural-source synthesized hydroxyapatite (HAp) nanoparticles and zinc oxide (ZnO) particles using the electrophoretic deposition technique. The goal was to create a multifunctional surface that could simultaneously accelerate bone growth and reduce the risk of infection. Five groups of coatings were prepared with different weight percentages of HAp and ZnO: 100:0, 75:25, 50:50, 25:75, and 0:100. The co-deposition was conducted on Ti6Al4V sheets for 5 min at a voltage of 90 V. The microstructure and phase composition of the synthesized powders were first analyzed. Then, the properties of the co-deposited coatings were evaluated through bioactivity and antibacterial tests. The microstructural investigation revealed crack-free coatings with a uniform distribution of particles. Comparing the antibacterial results among different groups indicated that the 50:50, 25:75 and 0:100 HAp/ZnO samples exhibited antibacterial activity against both Escherichia coli and Staphylococcus aureus. In contrast, the 100:0 and 75:25 samples showed no activity against Escherichia coli and negligible activity against Staphylococcus aureus. Additionally, all coatings demonstrated bonelike apatite formation on their surfaces in simulated body fluid, confirming their in vitro bioactivity, which was highest for 100:0 sample. The results also confirmed a synergistic effect, where HAp contributed to antibacterial properties and ZnO enhanced bioactivity in the co-deposited samples.